Left Atrial Appendage Electrical Isolation Reduces Atrial Fibrillation Recurrences: A Simulation Study. (January 2021) - Gharaviri, Ali; Pezzuto, Simone; Potse, Mark; Verheule, Sander; Conte, Giulio; Krause, Rolf; Schotten, Ulrich; Auricchio, Angelo
Abstract : Supplemental Digital Content is available in the text.